ผลของโปรแกรมส่งเสริมการรับรู้สมรรถนะแห่งตนต่อพฤติกรรมการฟื้นฟูสภาพของผู้ป่วยกระดูกขาหักที่ได้รับการผ่าตัดใส่โลหะยึดตรึงภายใน - นันทยา เสนีย์ (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
This quasi - experimental study aims to examine the effect of the Perceived Self-Efficacy Promoting Program on rehabilitation behavior in patients with femoral fracture receiving internal fixation. The participants were 50 patients with femoral fracture receiving internal fixation at Trang hospital. The first 25 patients were assigned to a control group and another twenty five were in an experimental group. Both groups were matched in term of gender, age, and level of education. The control group received conventional nursing care where as the experimental group joined the 8-week perceived self-efficacy promoting program. Data collection instruments were demographic and rehabilitation behaviors questionnaires. Content validity of the questionnaires was validated by five experts. Internal consistency reliability determined by Cronbach s alpha coefficients was 0.88. Data were analyzed using mean, percentage, standard deviation, and independent t-test.The findings were presented as follows: The mean score of rehabilitation behaviors of the experimental group was significantly higher than that of the control group (p < .05).